Comparative Analysis of Elementary Mathematics Textbooks on Geometry in Indonesia and the United States - Puspitaningrum, Rifky; Purnomo, Yoppy Wahyu (Jurnal Pendidikan Progresif, 2025)
Comparative Analysis of Elementary Mathematics Textbooks on Geometry in Indonesia and the United States. Objectives: This study aims to describe a comparison between elementary mathematics textbooks from Indonesia and the United States, focusing on geometry content. The analysis covers mathematical content based on Van Hiele’s levels of geometric thinking and Gracins’ framework, including mathematical activities, task complexity levels, response formats, and contextual features. Methods: A qualitative approach was employed, using coding and content recording techniques on Indonesian mathematics textbooks (Matematika SD/MI) and the Go Math! series from the United States across all elementary grade levels. Horizontal and vertical analyses were conducted. Inter-rater reliability was tested using Fleiss’ Kappa via JASP software, yielding high agreement levels ranging from "almost perfect" to "substantial" across all dimensions. Findings: The results indicate that Go Math! has a greater number of pages, emphasizes reasoning and conceptual connections, and is dominated by closed-ended tasks. Indonesian textbooks tend to focus more on geometric shapes and properties, with a stronger presence of realistic contextual applications. Notably, there is no geometry content in Go Math! Grade 6 (2023 edition). Conclusion: This study contributes to the international discourse on textbook design and curriculum policy. The comparison reveals differing instructional approaches to geometry between developing and developed countries. The applicability of the Van Hiele and Gracins’ frameworks across educational contexts is affirmed. Differences in contextual features also highlight the influence of local culture on mathematical content presentation. The absence of geometry in the final elementary grade in the U.S. curriculum points to a potential learning gap. This study recommends the development of more progressive mathematics textbooks that include varied activities, open-ended tasks, and meaningful contexts. It also encourages further comparative research across different content domains as a foundation for global mathematics education reform. Keywords: textbook research, mathematics, geometry, indonesia, united states.